CORR® ORS Richard A. Brand Award: Disruption in Peroxisome Proliferator-Activated Receptor-γ (PPARG) Increases Osteonecrosis Risk Through Genetic Variance and Pharmacologic Modulation. Issue 8 (August 2019) - Wyles, Cody C.; Paradise, Christopher R.; Houdek, Matthew T.; Slager, Susan L.; Terzic, Andre; Behfar, Atta; van Wijnen, Andre J.; Sierra, Rafael J.
Abstract: Background: The pathophysiology of osteonecrosis of the femoral head (ONFH) is poorly understood, and the diagnosis is idiopathic in as many as 40% of patients. Genetic and epigenetic etiologies have been postulated, yet no single nucleotide polymorphisms (SNPs) with intuitive biologic implications have been elucidated. Questions/purposes: (1) Do individuals with ONFH share common biologically relevant genetic variants associated with disease development? (2) What is the mechanism by which these SNPs may impact the expression or function of the affected gene or protein? Methods: This retrospective genome-wide association study (GWAS) evaluated participants from the Mayo Clinic Biobank and Mayo Clinic Genome Consortium between August 2009 and March 2017. We included every patient with atraumatic ONFH in each of these respective registries and every control patient in a previous GWAS with an acceptable platform to perform statistical imputation. The study was performed in two phases, with an initial discovery cohort and a subsequent validation cohort. The initial discovery cohort consisted of 102 patients with ONFH and 4125 controls. A logistic regression analysis was used to evaluate associations between SNPs and the risk of ONFH, adjusted for age and sex. Seven SNPs were identified in a gene of biological interest, peroxisome proliferator-activated receptor gamma ( PPARG ), which were then evaluated in a subsequent validation cohort of 38 patients with ONFH and 464 controls. Age, sex, race, and previous steroid exposure were similar between patients with ONFH and controls in both the discovery and validation cohorts. Separate from the two-phase genetic investigation, we performed targeted pharmacosurveillance to evaluate the risk association between the use of antidiabetic thiazolidinediones, a class of PPARG agonists, and development of ONFH by referencing 9, 638, 296 patient records for individuals treated at Mayo Clinic. Results: A combined analysis of the discovery and validation cohorts revealed that seven SNPs were tightly clustered adjacent to the 3' end of PPARG, suggesting an association with the risk of ONFH (p = 1.58 x 10 -2 -5.50 x10 -6 ). PPARG gene-level significance was achieved (p = 3.33 x 10 -6 ) when all seven SNPs were considered. SNP rs980990 had the strongest association with the risk of ONFH (odds ratio [OR], 1.95; 95% CI, 1.46-2.59; p = 5.50 x 10 -6 ). The seven identified SNPs were mapped to a region near the PPARG gene and fell in a highly conserved region consisting of several critical transcription factor binding sites. Nucleotide polymorphisms at these sites may compromise three-dimensional chromatin organization and alter PPARG 3' end interactions with its 5' promoter and transcription start site. Pharmacosurveillance identified that patients who were exposed to thiazolidinediones had an increased relative risk of developing ONFH of 5.6 (95% CI, 4.5-7.1). Conclusions: We found that disruption of PPARG regulatory domains is linked to an increased risk of ONFH. Mechanistically, aberrant regulation of PPARG compromises musculoskeletal differentiation because this master regulator creates a proadipogenic and antiosteogenic state. Furthermore, PPARG alters steroid metabolism and vasculogenesis, processes that are inextricably linked with ONFH. Pharmacologically, predisposition to ONFH was further exposed with thiazolidinedione use, which upregulates the expression of PPARG and is known to alter bone metabolism. Collectively, these findings provide a foundation to perform confirmatory studies of our proposed mechanism in preclinical models to develop screening diagnostics and potential therapies in patients with limited options. Level of Evidence: Level III, prognostic study.